2023
DOI: 10.3390/nu15092063
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transport of Artificial Sweeteners

Abstract: The prevalence of obesity is increasing, and the origins of obesity and metabolic dysfunction may be traced back to fetal life. Currently, overweight pregnant women are advised to substitute sugar-sweetened beverages with diet drinks containing artificial sweeteners. Recent evidence suggests that the consumption of artificial sweeteners during pregnancy increases the risk of obesity in the child, but the mechanism is unknown. We hypothesized the transportation of artificial sweeteners across the placenta into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It also might cause several aspects during early life stages such as low IQ (Sharma et al, 2016). Studies on humans showed that many AS such as sucralose, acesulfame K, cyclamate, and saccharine cross the placenta (Aguayo-Guerrero et al, 2023;Leth-Møller et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It also might cause several aspects during early life stages such as low IQ (Sharma et al, 2016). Studies on humans showed that many AS such as sucralose, acesulfame K, cyclamate, and saccharine cross the placenta (Aguayo-Guerrero et al, 2023;Leth-Møller et al, 2023).…”
Section: Discussionmentioning
confidence: 99%